Hormonal Contraceptives and Athletic Outcomes - analysis of potential effects of oral contraceptives on strength, endurance, mood, and overall competitive results - Lewandowska, Dominika; Rosińska-Lewandoska, Dominika; Strep, Dominika; Podraza, Anna; Grabowska, Julia; Kwiatkowski, Maciej; Romańczyk, Patryk; Białczak, Julia; Kanownik, Weronika; Rosiński, Jakub (Journal of Education, Health and Sport, 2025)
Introduction Hormonal contraceptives, particularly oral contraceptives (OC), are commonly used by female athletes to regulate menstrual cycles, manage hormonal fluctuations, and prevent unwanted pregnancies. With an increasing number of women competing at elite levels, a central question emerges: can OC use influence key aspects of performance—such as strength, endurance, and mood stability—and thereby affect competitive outcomes? Analysis of the Literature Findings regarding the impact of OC on athletic outcomes remain inconsistent. Some investigators report slight reductions in muscle strength and cardiorespiratory capacity, possibly linked to hormonal shifts or metabolic alterations. Others note minimal or negligible changes, pointing to variables such as training volume, sport-specific demands, and the athlete’s inherent physiological profile. Additionally, certain studies underscore potential mood-related benefits, including more stable emotional states that might support training compliance. These varying conclusions highlight the multifactorial nature of OC use, emphasizing the importance of personalization and monitoring to capture individual responses. Conclusions Overall, the relationship between oral contraceptive use and athletic performance is complex and appears to be highly individualized. While some athletes may observe modest shifts in physical or psychological parameters, others remain largely unaffected. Further, well-controlled research is needed to clarify these effects, enabling more targeted guidance for both athletes and healthcare professionals.